Heterozygous Nme7 Mutation Affects Glucose Tolerance in Male Rats - Šedová, Lucie (Genes (Basel), 2021)
Complex metabolic conditions such as type 2 diabetes and obesity result from the interaction of numerous genetic and environmental factors. While the family of Nme proteins has been connected so far mostly to development, proliferation, or ciliary functions, several lines of evidence from human and experimental studies point to the potential involvement of one of its members, NME7 (non-metastatic cells 7, nucleoside diphosphate kinase 7) in carbohydrate and lipid metabolism. As a complete lack of Nme7 is semilethal in rats, we compared morphometric, metabolic, and transcriptomic profiles of standard diet-fed heterozygous Nme7+/− on male rats vs. their wild-type Nme7+/+ controls. Nme7+/− animals showed increased body weight, adiposity, higher insulin levels together with decreased glucose tolerance. Moreover, they displayed pancreatic islet fibrosis and kidney tubular damage. Despite no signs of overt liver steatosis or dyslipidemia, we found significant changes in the hepatic transcriptome of Nme7+/− male rats with a concerted increase of expression of lipogenic enzymes including Scd1, Fads1, Dhcr7 and a decrease of Cyp7b1 and Nme7. Network analyses suggested possible links between Nme7 and the activation of Srebf1 and Srebf2 upstream regulators. These results further support the implication of NME7 in the pathogenesis of glucose intolerance and adiposity.